Pembatalan Perkawinan Poligami di Pengadilan Agama (Tinjauan Dari Hukum Positif) - Hotnidah Nasution (Jurnal Cita Hukum, 2013)
Nullity Polygamy in the Religious Court. According to the positive law in Indonesia, Muslim husband may practice polygamy, and the polygamy can be recorded at the Office of Religious Affairs (KUA) if he got permission from the Religious Court. If permission is not obtained from the Religious Court, then according to the provisions of article 44 of Government Regulation No. 9 of 1975 the marriage can not be authorized. Therefore, if polygamous marriages is recorded by the KUA when marriages have permission from a religious court. DOI: 10.15408/jch.v1i1.2986